Restoration of skeletal muscle function via mesenchymal stem cells: mechanistic insights and therapeutic advances in myasthenia gravis - Zhang, Xinyi; Zhang, Dongmei; Zhang, Ying; Wang, Jian; Lu, Jing (Frontiers in Cell and Developmental Biology, 2025)
Mesenchymal stem cells (MSCs) have demonstrated distinct advantages in skeletal muscle repair owing to their self-renewal capacity, multidirectional differentiation potential, and immunomodulatory functions. As a critical regulator of skeletal muscle regeneration, MSCs have been shown to ameliorate skeletal muscle injury induced by factors such as wasting and metabolic disorders through the activation of satellite cell function, inhibition of myofiber atrophy, and regulation of protein metabolic balance. In the treatment of myasthenia gravis (MG), the therapeutic effects of MSCs are exerted through dual mechanisms: first, autoantibody production is reduced via immunomodulation, thereby alleviating immune-mediated attacks at neuromuscular junctions; second, secondary muscle atrophy is delayed by preserving the integrity of neuromuscular signaling. Notably, MSC function is closely associated with acetylcholine metabolism, neuromuscular junction stability, and the aging microenvironment, in which aging-induced MSC decline may exacerbate intramuscular fat infiltration and impair regenerative capacity. In this paper, the biological properties of mesenchymal stem cells (MSCs) and their regulatory roles in skeletal muscle metabolic and injury-related abnormalities are systematically reviewed, and the fundamental significance of MSCs in skeletal muscle repair and myasthenia gravis (MG) therapy is elucidated through multiple mechanisms, including immunomodulation, neuroprotection, and muscle fiber regeneration. Furthermore, the bottlenecks of clinical translation (including cell source selection, phenotypic stability, and efficacy heterogeneity) are analyzed, and the challenges and optimization strategies for clinical application are discussed, with the aim of providing theoretical references for regenerative medicine research in neuromuscular diseases. However, clinical translation studies have indicated that the actual efficacy of most MSC-based therapies is considerably lower than that observed in in vitro experiments. This discrepancy may be attributed to low post-transplantation cell survival, inadequate homing efficiency, and the adverse influence of a senescent microenvironment that impairs cellular function. It has been indicated by recent studies that strategies, including optimization of cell sources and preparation protocols (e.g., the use of allogeneic MSCs derived from adipose tissue or umbilical cord with standardized production), incorporation of biomaterial supports (such as hydrogel-based encapsulation), and adoption of combination therapies (e.g., co-administration with neurotrophic factors or targeted drugs), can effectively improve the delivery efficiency and therapeutic outcomes of MSCs.